New Teacher Identity and Regulative Government - Brown, Tony. author. aut Link
X, 208 p.
Keywords: This book offers a unique theoretical perspective deploying contemporary psychoanalytical and post-structuralist theory in an easy accessible style. It links issues in education research, with a particular emphasis on mathematics, to broader social concerns and theorising. This volume documents in real time the implementation of a major government numeracy programme and its receipt by trainee and new teachers. It shows how such managerialist policies cast teachers as civil servants through de-professionalising the conception of their role. The book provides an easy and accessible commentary utilising contemporary theory to describe how such teachers reconcile their personal aspirations with the external demands they encounter in negotiating their identities as professional teachers. It shows how recent advances in psychoanalytic and post-structuralist theory enable a fresh approach to analysing teacher experience of and response to policy implementation. And more broadly, by situating education in a wider social framework, it shows how we can better formulate solutions to new problems in conceptualising education policy. The twentieth century has left a legacy of techno-scientific control governed by the ideology of "real" social forces. As we begin to experience a new century where such rationalistic aspirations have been re-routed in so many areas of theory the book asks how education research might move on from these earlier instrumentalist tendencies. This volume will be of interest to researchers in mathematics education, teacher education, policy implementation, contemporary theory and psychoanalysis in education as well as to student teachers, teacher educators, teachers carrying out in-service training and postgraduate students in education.